2015
DOI: 10.1104/pp.15.01543
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione regulates ACC synthase transcription via WRKY33 and ACC oxidase by modulating mRNA stability to induce ethylene synthesis during stress

Abstract: Glutathione (GSH) plays a fundamental role in plant defense-signaling network. Recently, we have established the involvement of GSH with ethylene (ET) to combat environmental stress. However, the mechanism of GSH-ET interplay still remains unexplored. Here, we demonstrate that GSH induces ET biosynthesis by modulating the transcriptional and posttranscriptional regulations of its key enzymes, 1-aminocyclopropane-1-carboxylate synthase (ACS) and 1-aminocyclopropane-1-carboxylate oxidase (ACO). Transgenic Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 104 publications
1
103
0
Order By: Relevance
“…The role of glutathione in regulating ACC synthase to induce ethylene in stress condition has already been established in our lab14. Ethylene and salicylic acid regulated the glutathione biosynthesis in ozone-exposed A. thaliana 15.…”
mentioning
confidence: 86%
“…The role of glutathione in regulating ACC synthase to induce ethylene in stress condition has already been established in our lab14. Ethylene and salicylic acid regulated the glutathione biosynthesis in ozone-exposed A. thaliana 15.…”
mentioning
confidence: 86%
“…Fu et al (2014) studied the regulatory interaction between S-assimilation and ethylene for tolerance to arsenic in Arabidopsis Col-0. Exogenously applied GSH positively modulates ethylene biosynthetic pathways enzyme and improves stress tolerance in Arabidopsis Col-0 showing that GSH mediated resistance to stresses occurs via an ethylene signaling pathway (Datta et al, 2015). Recent studies showed that ethylene signaling pathways might be involved in the accumulation of GSH under Cd stress (Guan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…AtWRKY33 is the homolog of VaWRKY33 , and is positive regulator of pathogen‐induced autophagy, which plays a critical role in plant resistance to necrotrophic fungal pathogens (Zheng et al ., ; Lai et al ., ), as well as being critical for abiotic stress tolerance (Jiang and Deyholos, ; Li et al ., ). Furthermore, AtWRKY33 plays an essential role in glutathione‐mediated transcriptional regulation of the key components of the ethylene signal pathway, ACS2 and ACS6, by binding to their promoters and promoting ethylene synthesis (Datta et al ., ). We infer from these observations that VaWRKY33 may also participate in the production of ethylene, resulting in enhanced cold tolerance.…”
Section: Discussionmentioning
confidence: 97%